2008
DOI: 10.1016/j.puhe.2008.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Local perspectives on humanitarian aid in Sri Lanka after the tsunami

Abstract: Objectives: This case study examines the impact of humanitarian aid from the perspectives of local stakeholders in Sri Lanka following the tsunami disaster of December 2004.Study Design: Qualitative study using key-informant and focus group interviews.Methods: Key-informant and focus group interviews were conducted with tsunami survivors, community leaders, the local authorities and aid workers sampled purposively. Data collected was analysed using thematic analysis.Results:The study found that aid had aggrava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 14 publications
1
25
0
1
Order By: Relevance
“…This accords with previous research in occupational settings, which found that met expectations were associated with high job satisfaction, performance and longevity (Wanous et al 1992). Conversely, when expectations are not met, levels of satisfaction and personal accomplishment decrease (Delgatty 2011;Lee 2008). Achievement expectations have not been specifically examined in HA worker populations, although related work has found that HA workers with high levels of motivation are less likely to suffer from burnout .…”
Section: Motivation and Achievementsupporting
confidence: 82%
“…This accords with previous research in occupational settings, which found that met expectations were associated with high job satisfaction, performance and longevity (Wanous et al 1992). Conversely, when expectations are not met, levels of satisfaction and personal accomplishment decrease (Delgatty 2011;Lee 2008). Achievement expectations have not been specifically examined in HA worker populations, although related work has found that HA workers with high levels of motivation are less likely to suffer from burnout .…”
Section: Motivation and Achievementsupporting
confidence: 82%
“…The fragmented multi-agency nature of the disaster management system often leads to problems of coordination as well as ineffectual and inefficient disaster responses which characterize numerous disasters worldwide. (23)(24)(25) The striking finding of this study was the demand echoed by respondents for strong policy direction and leadership, as well as a supportive legislative framework that is implemented and enforced. These politico-legal aspects are key components of the disaster management system, acting as both catalyst and facilitating agent.…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, recovery and mitigation issues are frequently overlooked [13,16]. There are various issues specific to these other phases, such as psychosocial trauma, community cohesion, and the health impacts of poorly managed incidents that are often inadequately documented and studied [24]. …”
Section: Discussionmentioning
confidence: 99%